SERUM ADIPONECTIN AND OTHER PREDICTORS OF NEED FOR INSULIN THERAPY IN GESTATIONAL DIABETES MELLITUS: A PILOT STUDY - MR, Shazatul Reza; Ratnasingam, J; Paramasivam, SS; Ibrahim, L; Lim, QH; Chiong, T Peng; Omar, S.Z.; Lim, LL; Vethakkan, SR (Journal of the ASEAN Federation of Endocrine Societies, 2021)
INTRODUCTION The prevalence of gestational diabetes mellitus (GDM) is increasing in Malaysia. Adiponectin is an adipokine that is expressed in adipose tissues and placenta. Plasma adiponectin levels are decreased in several metabolic disorders, including obesity, inflammatory states, insulin resistance, and type 2 diabetes. To our knowledge, there are no published reports on the association between plasma adiponectin levels and need for insulin therapy in GDM. The aim of this study was to assess the association of 1) adiponectin and 2) other predictors such as BMI and HbA1c; with the need for insulin therapy in GDM. METHODOLOGY In this prospective pilot study, we recruited women with GDM from combined antenatal clinic. Demographic, anthropometric and clinical data were obtained during the interview. Blood was drawn for insulin, c-peptide, adiponectin and triglyceride at recruitment. RESULTS Of the 142 women included in this study, 16.2% required insulin therapy and 83.8% of patients were able to maintain adequate glycaemic control with diet. We did not find adiponectin at GDM diagnosis to be a significant predictor of need for insulin therapy in both univariate and multivariate analyses. The most robust significant correlation of adiponectin in mothers with GDM (r >0.5) was an inverse association with HOMA IR and fasting insulin which is reflective of insulin resistance. Significant associations of insulin requirement in univariate analysis included history of GDM, history of insulin-requiring GDM and glycaemic variables at diagnosis (higher fasting, 2-hour glucose, AUC glucose). Upon multivariate analysis after adjusting for pre-pregnancy BMI and maternal insulin resistance, only Chinese ethnicity (OR= 4.17, CI 1.32-13.16), history of GDM requiring insulin therapy (OR 10.67, CI 1.78-63.90), and AUC glucose (OR=2.14, CI 1.32- 3.45) were significantly associated with increased need for insulin therapy. CONCLUSION Women with GDM who have an elevated AUC glucose, previous insulin-requiring GDM and are of Chinese ethnicity are at higher risk of requiring insulin therapy.